AKTIVITAS KOMUNIKASI PARIWISATA DINAS PARIWISATA KOTA MAKASSAR DALAM PROGRAM SUSTAINABLE TOURISM DI PANTAI TANJUNG BAYANG KOTA MAKASSAR - Rohmadani , Anisa; Zelfia, Zelfia; Rabiah , Sitti (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
Tourism communication is an activity that intends to influence, urge and seduce potential tourists as consumers to make decisions to make tourist trips. The tourism communication that the writer wants to examine is about tourism communication activities carried out by the Makassar City Tourism Office with the manager of Tanjung Bayang Beach, Makassar City. In this study, the author uses a qualitative research methodology to describe tourism communication activities carried out by the Makassar City Tourism Office. Data collection techniques were carried out through interviews, direct observation and documentation. The validity of the data is checked, then the presentation and analysis of the data is carried out and then conclusions are drawn. Based on the results of the research, the Makassar City Tourism Office and the Makassar City Tanjung Bayang Beach manager are expected to continue to pay attention to the consistency of the sustainability of tourist destinations through the implementation of the Sustainable Tourism. In addition, researchers hope that this work can be used as a study material to find a formula for sustainable tourism development.